(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Adventure tourism is defined as the movement of the people from one to another place outside their comfort zone for exploration or travel to remote areas, exotic and possibly hostile areas. Adventure tourism is a type of tourism in which tourist do some adventures activities like as skydiving, hill climbing, scuba diving.